PET probe detecting non-small cell lung cancer susceptible to epidermal growth factor receptor tyrosine kinase inhibitor therapy. Issue 8 (1st May 2018) - Makino, Akira; Miyazaki, Anna; Tomoike, Ayaka; Kimura, Hiroyuki; Arimitsu, Kenji; Hirata, Masahiko; Ohmomo, Yoshiro; Nishii, Ryuichi; Okazawa, Hidehiko; Kiyono, Yasushi; Ono, Masahiro; Saji, Hideo
Graphical abstract: Abstract: Tyrosine kinase inhibitors for epidermal growth factor receptor (EGFR-TKIs) are used as molecular targeted therapy for non-small cell lung cancer (NSCLC) patients. The therapy is applied to the patients having EGFR-primary L858R mutation, but drug tolerance caused by EGFR-secondary mutation is occurred within one and half years. For the non-invasive detection of the EGFR-TKIs treatment positive patients by positron emission tomograpy (PET) imagaing, fluorine-18 labeled thienopyrimidine derivative, [ 18 F]FTP2 was newly synthesized. EGFR inhibition assay, cell uptake study, and blocking study indicated [ 18 F]FTP2 binds with high and selective affinity for EGFR with L858R mutation, and not with L858R/T790M dual mutations. On animal PET study using tumor bearing mice, H3255 cells expressing L858R mutated EGFR was more clearly visualized than H1975 cells expressing L858R/T790M dual mutated EGFR. [ 18 F]FTP2 has potential for detecting NSCLC which is susceptible to EGFR-TKI treatment.